Stalin and the Pamphlet “Falsifiers Of History”: “Interpretations”, Guidelines and Their Implementation. - Szumski, Jan; Musiał, Bogdan (Institute of National Remembrance Review, 2022)
The article focuses on the background of the pamphlet ‘Falsifiers of History. An Historical Note’ issued by the Soviet Information Bureau in 1948. The book was personally edited and largely hand-written by Joseph Stalin. His involvement was not fully known until now. In this paper, the authors deciphered, translated and compared the text of the published pamphlet. It shows Stalin’s guidelines in the official interpretation of the causes of World War II and the reasons for the signing of the Molotov-Ribbentrop Pact. Throughout the post-war period the official Soviet narrative regarding the origins of the of World War II were largely based on a set of guidelines contained in a pamphlet ‘Falsifiers of History’. Currently, the neo-Stalinist historical narrative concerning the origins of World War II is promoted by the Russian officials. Nevertheless, not all Russian historians share these views, and many assess the Hitler-Stalin Pact in a much more critical way.